MACROMYCETES PARKU W MAŁKOCINIE (NW POLSKA) - Kwiatkowska, Justyna (Badania Fizjograficzne Seria B - Botanika, 2020)
The paper presents the results of mycological research carried out in the manor Małkocin park (NW Poland) in the years 2008–2009. During 35 observations, 200 species of macromycetes (mainly Basidiomycota – 172 species) and four Myxycomycota have been recorded. Among them, 11 species are included on the red list of macrofungi in Poland. The participation of macrofungi was analyzed in bioecological groups of saprotrophic, mycorrhizal and parasitic fungi. In addition, the comparison of the Małkocin park with other rural parks of Poland is discussed.